Upper Motor Neuron Signs in the Cervical Region of Patients With Flail Arm Syndrome - Xu, Yingsheng; Chen, Junyi; Zhang, Shuo; Fan, Dongsheng (Frontiers in Neurology, 2021)
Objective: We investigated upper motor neuron (UMN) signs in the cervical region in a Chinese clinic-based cohort of patients with flail arm syndrome (FAS) by clinical examination and neurophysiological tests such as triple stimulation technique (TST) and pectoralis tendon reflex testing. Methods: A total of 130 consecutive FAS patients from Peking University Third Hospital underwent physical examination and neurophysiological tests at baseline and 3 months, 6 months, 9 months and 12 months later. Pyramidal signs, pectoralis tendon reflex and TST results were evaluated to estimate the function of cervical spinal UMNs. Results: At the time of diagnosis, weakness of the bilateral proximal upper limbs was found in 99 patients, while weakness of a single proximal upper limb was found in 31 patients. There were 49 patients with tendon hyperreflexia, 42 patients with tendon hyporeflexia and 39 patients with tendon areflexia. All except 4 of the patients had brisk pectoralis tendon reflex. The UMN score of the cervical region was 1.7±0.4, and the lower motor neuron score of that region was 3.5±0.3. The TSTtest/TSTcontrol amplitude ratio was 65.7±7.5%. The latency of quantitative detection of the pectoralis tendon reflex was 7.7±1.2 ms. In the follow-up study, the UMN score and the TSTtest/TSTcontrol amplitude ratio decreased, while the lower motor neuron score increased, and the latency of quantitative detection of the pectoralis tendon reflex remained steady. Conclusion: Although the signs of cervical spinal UMN dysfunction in patients with FAS were often concealed by muscle atrophy in the progression of the disease, TST and pectoralis tendon reflex could reveal it.